Synergism between mechanical wear and corrosion on tribocorrosion of a titanium alloy in a Ringer solution - Danilo Fontes Ferreira; Sérgio Matheus Ale Almeida; Renata Braga Soares; Luciano Juliani; Alexandre Queiroz Bracarense; Vanessa de Freitas Cunha Lins; Rosa Maria Rabelo Junqueira (Journal of Materials Research and Technology, 2019)
The tribocorrosion behavior of a biocompatible ASTM-F67Gr1 titanium alloy was evaluated. An experimental pin-on-flat reciprocating sliding tribo-electrochemical setup was built which allowed the investigation of tribocorrosion phenomena in an electrolyte of a Ringer solution. Tests were performed at anodic and cathodic potential, and at two values of applied load and sliding speed. Potentiodynamic tests indicated a corrosion potential of −0.368 ± 0.082 VSCE and a passivation range between 0.344 VSCE and 2.932 VSCE was observed. After polarization tests, no pits were identified on the titanium alloy. The volume of worn material was higher at an anodic potential than in a cathodic potential, especially for the condition of the highest applied load and speed. Higher metal losses at a cathodic potential (pure mechanical wear) were observed in conditions of the highest speed. The mass loss due to the corrosion was similar for all conditions, and the synergistic factor was the highest for the condition of the highest applied load and sliding speed. Keywords: Tribocorrosion, Titanium, Biomaterials, Potentiodynamic tests, Ringer solution